2014
DOI: 10.1007/s00228-014-1770-2
|View full text |Cite
|
Sign up to set email alerts
|

N1-methylnicotinamide as an endogenous probe for drug interactions by renal cation transporters: studies on the metformin–trimethoprim interaction

Abstract: These data on the metformin-trimethoprim interaction support the potential utility of N(1)-methylnicotinamide as an endogenous probe for renal drug-drug interactions with involvement of renal cation transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 30 publications
5
132
0
Order By: Relevance
“…The [I] 1 /IC 50 values for ketoconazole and the sum of these values for itraconazole and its metabolites were .100-fold the cutoff value for OCT1. Although few reports show that the pharmacokinetics of OCT1 substrates are altered by OCT1 inhibitors (Cho et al, 2014;Müller et al, 2015), the high [I] 1 /IC 50 values for OCT1 reported in this work may be clinically relevant for some substrates of OCT1. For instance, verapamil was found to have an IC 50 value of 12.5 mM toward OCT1-mediated metformin transport, with an [I] 1 /IC 50 value of only 0.048 (Ahlin et al, 2011;University of Washington, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…The [I] 1 /IC 50 values for ketoconazole and the sum of these values for itraconazole and its metabolites were .100-fold the cutoff value for OCT1. Although few reports show that the pharmacokinetics of OCT1 substrates are altered by OCT1 inhibitors (Cho et al, 2014;Müller et al, 2015), the high [I] 1 /IC 50 values for OCT1 reported in this work may be clinically relevant for some substrates of OCT1. For instance, verapamil was found to have an IC 50 value of 12.5 mM toward OCT1-mediated metformin transport, with an [I] 1 /IC 50 value of only 0.048 (Ahlin et al, 2011;University of Washington, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…From the literature we know that inhibitors of OCT and MATE can have a clinically relevant impact on the pharmacokinetics of concomitantly administered organic cations through reduction in their renal clearance (14,15,23). Known inhibitors are cimetidine for OCT2 (IC 50 of 110 M [24]) and MATE1/MATE2K (K i of 7 and 1 M, respectively [25]) as well as pyrimethamine for OCT2 (K i of 10 M [15]) and MATE1/ MATE2K (K i of 93 and 59 nM, respectively [15]).…”
Section: Discussionmentioning
confidence: 99%
“…18 Overall, these transporters mediate the cellular influx of structurally diverse compounds and greatly impact on the pharmacokinetics of drugs in body. Drugs and endogenous substances competing for SLC transporters have also been widely reported, [19][20][21] and can significantly impact on therapeutic outcomes and toxicities. To date, the interactions between SLC transporters and CQ or HCQ remain unclear.…”
Section: Introductionmentioning
confidence: 99%